2018
DOI: 10.1038/s41598-018-35266-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Binding of Allosteric Drug Leads in the Adenosine A1 Receptor

Abstract: Despite intense interest in designing positive allosteric modulators (PAMs) as selective drugs of the adenosine A1 receptor (A1AR), structural binding modes of the receptor PAMs remain unknown. Using the first X-ray structure of the A1AR, we have performed all-atom simulations using a robust Gaussian accelerated molecular dynamics (GaMD) technique to determine binding modes of the A1AR allosteric drug leads. Two prototypical PAMs, PD81723 and VCP171, were selected. Each PAM was initially placed at least 20 Å a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 72 publications
(127 reference statements)
6
73
0
Order By: Relevance
“…In contrast, this lysine pointed towards ECL2 in the active A1AR. This was consistent with our previous study (66) , in which the positive allosteric modulator (PAM) enhanced the agonist binding at the orthosteric site by forming a salt-bridge between E172 ECL2 -K265 ECL3 . Moreover, the active A1AR attracted more lipids in the lower leaflet compared with the inactive A1AR.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, this lysine pointed towards ECL2 in the active A1AR. This was consistent with our previous study (66) , in which the positive allosteric modulator (PAM) enhanced the agonist binding at the orthosteric site by forming a salt-bridge between E172 ECL2 -K265 ECL3 . Moreover, the active A1AR attracted more lipids in the lower leaflet compared with the inactive A1AR.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, this lysine pointed toward ECL2 in the active A 1 AR. This was consistent with our previous study, in which the positive allosteric modulator (PAM) enhanced the agonist binding at the orthosteric site by forming a salt‐bridge between E172 ECL2 ‐K265 ECL3 . Moreover, the active A 1 AR attracted more lipids in the lower leaflet compared with the inactive A 1 AR.…”
Section: Discussionsupporting
confidence: 93%
“…Both experimental and computational studies suggested that flexibility of the ECL2 was important for activation and allosteric modulation of the A1AR. 39,44,45 Therefore, highly flexibility of the ECL2 contributed to activation of the A1AR and receptor coupling to the G protein.…”
Section: Mechanism Of Specific Adenosine Receptor-g Protein Interactimentioning
confidence: 99%